Clinical Evaluation of Carbamide Peroxide and Hydrogen Peroxide as Vehicle of Intracoronal Bleaching Agent in A3 or Darker Shaded Discolored Teeth (Journal of Dentistry and Allied Science, 2025)
Introduction: 10% carbamide peroxide gel has been tried as an alternative intracoronal bleaching agent and it was found effective. The objectives of the study were to evaluate and compare the efficacy of carbamide peroxide and hydrogen peroxide as vehicle of dental bleaching agents when mixed with sodium perborate powder in patients having teeth of A3 or darker shades. Materials and methods: On the basis of predetermined inclusion and exclusion criteria, 11 patients could be scrutinized whose teeth shade were A3 or darker than A3. According to the bleaching agents to be evaluated, patients were allocated under 2 groups. The shade of adjacent normal tooth was used as control. Preoperative and postoperative color assessments of the discolored teeth were done weekly by three clinicians independently using a standard clinical shade guide. Evaluation was continued up to achieving the shade of the adjacent control tooth or a maximum of 5 weeks by using a scale of evaluation. Collected data of the weekly efficacy score were analyzed using a statistical software SPSS version 11.5. Results: The difference of treatment outcome between the groups on the study patients after 5 weeks of treatment was not statistically significant and also, neither of the two bleaching agents was significantly superior to each other in changing the shades among the patients having A3/darker shades. On comparing the weekly average efficacy score pattern between the groups, Hydrogen peroxide group revealed statistically significant score at the end of 4th week while at the same time Carbamide peroxide group revealed its most unsatisfactory score. Conclusions: Within the study period, both the bleaching agents were able to bleach satisfactorily all the patients up to the desired normal shade. While comparing average efficacy score after 5 weeks, there was no statistically significant difference between the materials.Journal of Dentistry and Allied Science, Vol. 7 No 2: 33-40